Institutional Influence of Academics in Argentinean Public Universities in a Context of External Control - Marquina, Mónica; Pérez Centeno, Cristian; Reznik, Nicolás (Acta Paedagogica Vilnensia, 2021)
The paper studies the institutional influence of academics in Argentina within a context of increasing external control as a consequence of deep public reforms in the Higher Education system. Drawing on data from the Academic Profession in the Knowledge-Based Society (APIKS) survey, the aim is to analyse how much and in what sense the recent changes on the public policy level and the intermediate level of the state agencies have affected the academic profession in Argentina over teaching, research and social engagement activities, and its effects over the perception of institutional influence. Although we assume that academic power has been reduced within the new scenario, we believe that not all academics have responded in the same manner.